DEVELOPMENT OF TEACHING BASED TEACHING MATERIALS TO IMPROVE STUDENTS 'DEVELOPMENT AND ACHIEVEMENT (Study on computer subjects and basic networks in Class X in Bengkulu City Vocational School) - Budi Riyanto; Alexon Alexon (DIADIK, 2019)
This research aims to describe, first the development of website-based teaching materials can improve student learning independence, secondly the development of website-based teaching materials can improve the learning achievement of computer lessons and basic student networks. This research uses Research and Development (R & D) research with Borg & Gall development model in class X TKJ Vocational High School 3 of Bengkulu City, Vocational High School 3 of Bengkulu City and Muhammadiyah 9th Vocational High School in the City of Bengkulu. This research uses steps, namely research and information collecting, planning, develop preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field testing, final product revision, implementation. The results of the research show that the development of website-based teaching materials can improve student independence and learning achievement.